The short ionizing photon mean free path at z = 6 in Cosmic Dawn III: a new fully coupled radiation-hydrodynamical simulation of the epoch of reionization - Lewis, Joseph; Ocvirk, Pierre; Sorce, Jenny G; Dubois, Yohan; Aubert, Dominique; Conaboy, Luke; Shapiro, Paul R; Dawoodbhoy, Taha; Teyssier, Romain; Yepes, Gustavo; Gottlöber, Stefan; Rasera, Yann; et al. (Monthly notices of the Royal Astronomical Society, 2022)
RRecent determinations of the mean free path of ionizing photons (mfp) in the intergalactic medium (IGM) at z = 6 are lower than many theoretical predictions. In order to gain insight, we investigate the evolution of the mfp in our new massive fully coupled radiation-hydrodynamics cosmological simulation of reionization: Cosmic Dawn III (CoDa III). CoDa III’s scale (943 cMpc3) and resolution (81923 grid) make it particularly suitable to study the IGM during reionization. ...
Online veröffentlicht am 25. August 2022
Gesehen am 12.10.2022